ChemInform Abstract: Co2(CO)8‐Mediated Cycloisomerization of Arylene 1, 7‐Enynes. Issue 23 (16th May 2013) - Xing, Ping; Huang, Zuo‐gang; Jin, Yun; Jiang, Biao
Abstract The title reaction renders possible the straightforward access to 2, 3‐dihydroindene derivatives.